Abbreviated MRI for Hepatocellular Carcinoma Screening and Surveillance - An, Julie Y. (Radiographics, 2020)
To detect potentially curable hepatocellular carcinoma (HCC), clinical practice guidelines recommend semiannual surveillance US of the liver in adult patients at risk for developing this malignancy, such as those with cirrhosis and some patients with chronic hepatitis B infection. However, cirrhosis and a large body habitus, both of which are increasingly prevalent in the United States and the rest of the world, may impair US visualization of liver lesions and reduce the sensitivity of surveillance with this modality. The low sensitivity of US for detection of early-stage HCC contributes to delayed diagnosis and increased mortality. Abbreviated MRI, a shortened MRI protocol tailored for early-stage detection of HCC, has been proposed as an alternative surveillance option that provides high sensitivity and specificity. Abbreviated MRI protocols include fewer sequences than a complete multiphase MRI examination and are specifically designed to identify small potentially curable HCCs that may be missed at US. Three abbreviated MRI strategies have been studied: (a) nonenhanced, (b) dynamic contrast material–enhanced, and (c) hepatobiliary phase contrast-enhanced abbreviated MRI. Retrospective studies have shown that simulated abbreviated MRI provides high sensitivity and specificity for early-stage HCC, mostly in nonsurveillance cohorts. If it is supported by scientific evidence in surveillance populations, adoption of abbreviated MRI could advance clinical practice by increasing early detection of HCC, allowing effective treatment and potentially prolonging life in the growing number of individuals with this cancer. Online supplemental material is available for this article. (©)RSNA, 2020